Efficacy of behavior modification training combined with electroencephalographic biofeedback therapy for attention deficit hyperactivity disorder in children: a randomized controlled trial - Luo, Xiangfen; Zhang, Ling; Xia, Lei; Zhou, Xiaoqin (Frontiers in Child and Adolescent Psychiatry, 2023)
Background and aims Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in children. Multiple treatments are currently available with varying effectiveness, and our aim was to investigate the efficacy of behavior modification training combined with Electroencephalography (EEG) biofeedback treatment on ADHD in children. Methods Children with ADHD were randomly divided into a control group (n = 42), an EEG biofeedback group (n = 30) and a behavior modification training combined with EEG biofeedback group (i.e., a combined intervention group) (n = 30) according to the intervention. Swanson, Nolan, and Pelham, Version IV (SNAP-IV) and Conners Parent Symptom Questionnaire (PSQ) were assessed before and after three months of treatment. Results We found that in the EEG biofeedback group and the combined intervention group, the scores of all factors except “anxiety” and “psychosomatic disorder” were lower than before treatment, and the difference was statistically significant (P < 0.05). After treatment, the scores of the three groups were compared. The scores of “impulsivity-hyperactivity”, “learning problems”, “inattention factor” and “hyperactivity factor” were all lower than before, and the difference was statistically significant (P < 0.05). In the post-treatment comprehensive intervention group and the control group, the efficacy was apparent, and the differences in the scores of each factor were statistically significant (P < 0.05). In the comparison between the EEG biofeedback group and the control group, except for “anxiety”, “psychosomatic disorder” and “conduct problem” the scores of each factor were statistically significant (P < 0.05). For the comparison between the integrated intervention group and the EEG biofeedback group, the scores of all factors before and after treatment were statistically significant (P < 0.05), except for “anxiety”, “impulsivity-hyperactivity” and the scores of all the factors before and after treatment were statistically significant (P < 0.05), except for “anxiety”, “impulsivity-hyperactivity” and “psychosomatic disorder”. Conclusions The comprehensive efficacy of behavior modification training combined with EEG biofeedback therapy on the improvement of symptoms in children with ADHD is positive, and good compliance is worthy of clinical promotion. Clinical Trial Registration https://www.chictr.org.cn/indexEN.html, identifier (ChiCTR2300071511).